In vitro radiosensitivity of lymphocytes from high-background radiation ar-ea inhabitants in Indonesia: a pilot study using the G0 micronucleus assay - Dwi Ramadhani; Sofiati Purnami; Siti Nurhayati; Eko Pudjadi; Mukh Syaifudin (The East Java Biological Society, 2018)
The Mamuju area has recorded a higher than average natural radiation dose compared to other regions in Indonesia. It is possible that inhabitants of Mamuju developed the radioadaptive response (RAR). To prove that the RAR was developed in Mamuju inhabitants, evaluation of lymphocytic radiosensitivity using the G0 micronucleus (MN) assay was conducted herein. The MN frequencies in peripheral blood lymphocytes before and after exposed to 1.5 Gy radiation at a dose rate of 0.38 Gy/min were assessed from 11 samples of Botteng Village, Mamuju inhabitants and control groups. These treated cells were then cultured and exposed to cytochalasin-B to arrest cells during the cytokinesis stage. The mean number of MN induced by radiation per 1000 binucleated cells (BNC) was evaluated for both Mamuju inhabitants and control groups. The lymphocytic radiosensitivity was calculated using standard deviation (SD) of the mean value (MV) of the number of MN induced by radiation found in the control group. Based on the SD and MV values, individual lymphocytes were classified as ‘‘resistant’’, ‘‘sensitive’’, or ‘‘normal’’ if the mean of MN induced by radiation was ≤ MV – (2×SD), ≥ MV + (2×SD) or in between, respectively. The results showed that lymphocytes from six samples in Botteng Village inhabitants were categorized as resistant and five samples were normal. In contrast, all samples in the control group were demonstrated to have normal sensitivities. The study results also revealed that lymphocytic radiosensitivity was not correlated with age and gender, which was probably because of the small sample size used in this study. Further investigation with a larger sample number and higher radiation dose should be conducted to validate our findings.